Communication-Aware Route Selection in Wireless Sensor Networks - Fida, Adnan (ĐHCN, 2016)
We consider the problem of optimal route selection for wireless sensor network in the presence of path loss, multipath fading, interference, and environmental noise. The communication-aware route selection strategy is proposed by incorporating realistic communication model portraying the underlying dynamics of wireless link. The link quality is characterized by the probability of successfully received packets over a communication link, so-called reception probability. We utilize reception probability as a metric for communication quality-oriented route selection and to compare its performance with the conventional metrics, i.e., Hop count and Euclidean distance. The simulation results demonstrate that reception probability-based route selection provides optimal end-to-end throughput in wireless sensor networks.